Possible role of circulating tumor cells in early detection of lung cancer - Poggiana, Cristina (J Thorac Dis, 2020)
The prognosis of lung cancer varies highly depending on the disease stage at diagnosis, from a 5-year survival rate close to 90% in stage I, to 10% or less in stage IV disease. The enhancement of early diagnosis of this malignancy is mandatory to improve prognosis, because lung cancer patients stay long asymptomatic or few symptomatic after disease onset. Nowadays, liquid biopsy has emerged as a minimally-invasive tool to address the urgent need for real time monitoring, stratification, and personalized treatment of malignancies, including lung cancer. Liquid biopsy refers to a class of biomarkers, including circulating tumor cells (CTCs), cell-free circulating tumor DNA (ctDNA) and tumor-derived extracellular vesicles (tdEV). Since CTCs represent a crucial step in disease progression and metastasis, we reviewed here the scientific literature about the use of CTCs in early diagnosis of lung cancer; different techniques, and different strategies (e.g., source of analysis sample or high-risk groups of patients) were discussed showing the potential of implementing liquid biopsy in the clinical routine of non-metastatic lung cancer.